2023
DOI: 10.1038/s41598-023-34667-x
|View full text |Cite
|
Sign up to set email alerts
|

Refraining from interaction can decrease fear of physical closeness during COVID-19

Abstract: Perception of peripersonal space (PPS) and interpersonal distance (IPD) has been shown to be modified by external factors such as perceived danger, the use of tools, and social factors. Especially in times of social distancing in the context of the COVID-19 pandemic, it is vital to study factors that modify PPS and IPD. The present work addresses the question of whether wearing a face mask as a protection tool and social interaction impact the perception of IPD. We tested estimated IPD in pictures at three dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…This finding underscores that this bias occurs only when interpersonal distance poses a threat. This interpretation is also supported by the research of Kühne and Jeglinski-Mende 44 , who found that at close proximity (i.e., 50 and 90 cm) people underestimated interpersonal distance in a third-party perspective. These researchers also interpreted this underestimation as a mechanism that is triggered by fear of infection and that promotes avoidance.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…This finding underscores that this bias occurs only when interpersonal distance poses a threat. This interpretation is also supported by the research of Kühne and Jeglinski-Mende 44 , who found that at close proximity (i.e., 50 and 90 cm) people underestimated interpersonal distance in a third-party perspective. These researchers also interpreted this underestimation as a mechanism that is triggered by fear of infection and that promotes avoidance.…”
Section: Discussionsupporting
confidence: 62%
“…Future studies should further investigate the role of subjective versus objective risk to clarify this point. Another inconsistency arises with Kühne and Jeglinski-Mende 44 , who demonstrated an underestimation of short distances and an overestimation of long distances. In the current study, however, the perception bias was calculated as an average of randomly chosen distances.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Another factor influencing IPD was the disparity between actual measurement and online simulation. Kühne and Jeglinski-Mende [29] found that participants tended to overestimate the distance in pictures at an IPD of 150 cm compared to 50 and 90 cm. This discrepancy may be due to the wider distance between individuals not being perceived as dangerous.…”
Section: Discussionmentioning
confidence: 98%